Regulation of Income Tax in Law Number 7 of 2021 in An Effort to Create Justice and Legal Certainty - Imron Chumaidi; Afif Noor (LEGAL BRIEF, 2022)
Income Tax Regulations in Law No. 7 of 2021 Concerning Harmonization of Tax Regulations has brought changes to the existence of income tax as a source of state revenue. One of the considerations for changing the Income Tax Law, in addition to increasing state revenues from the tax sector, is to provide justice and certainty for taxpayers. Justice and certainty are requirements for tax collection that must always be considered when drafting regulations in the taxation sector. This research will examine the income tax regulation in Law No. 7 of 2021 from the perspective of justice and legal certainty. Data mining is carried out using secondary data in the form of primary legal materials and secondary legal materials. Based on the data obtained, it can be concluded that the income tax regulation in Law No. 7 of 2021 has provided justice and legal certainty, which, among others, is indicated by the five layers of income tax and the widening of the range of taxable income (PKP).